Improvement of microseismic source location during cavern excavation in faulted rock mass using fast marching method. (October 2022) - Zhang, Jinyong; Xu, Nuwen; Wu, Wei; Xiao, Peiwei; Li, Biao; Dong, Linlu
Highlights: The FMM-based method is applied to the faulted rock mass to improve location accuracy of MS events. The FMM-based method performs better than the UVM-based method in several 3D velocity models. The wave paths from the method agree well with the analytical solution obtained by the Snell law. The MS source mechanisms of location results are analyzed through moment tensor inversion. Abstract: Understanding the temporospatial distribution of microseismic events is critical for the early warning of induced geohazards during deep rock excavation. However, the accuracy of microseismic source location can be influenced by many geological and engineering factors, such as rock discontinuities and excavated openings. This study addresses the application of fast marching method (FMM) to improve the location accuracy in faulted rock masses and takes a case of powerhouse excavation in the Shuangjiangkou hydropower project as an example. The FMM-based method includes five steps, such as inputs, gridding, velocity assignment, calculation, and output, and can be readily processed using a travel time database. Our results exhibit that the wave paths obtained from the FMM-based method are consistent with those from the analytical solution based on the Snell law and better than those from the commonly used uniform velocity model. The results also signify that the FMM-based method can improve the location accuracy for P-wave propagating across a low-velocity layer and an excavated opening. Moreover, this method can be further improved, such as reasonable determination of grid spacing and thorough detection of major discontinuities.